The Capabilities of Market-Driven Organizations - Day, George S. (Journal of Marketing, 1994)
Considerable progress has been made in identifying market-driven businesses, understanding what they do, and measuring the bottom-line consequences of their orientation to their markets. The next challenge is to understand how this organizational orientation can be achieved and sustained. The emerging capabilities approach to strategic management, when coupled with total quality management, offers a rich array of ways to design change programs that will enhance a market orientation. The most distinctive features of market-driven organizations are their mastery of the market sensing and customer linking capabilities. A comprehensive change program aimed at enhancing these capabilities includes: (1) the diagnosis of current capabilities, (2) anticipation of future needs for capabilities, (3) bottom-up redesign of underlying processes, (4) top-down direction and commitment, (5) creative use of information technology, and (6) continuous monitoring of progress.